2013
DOI: 10.1039/c3sm52115j
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of a moving contact line in a channel

Abstract: International audienceThe shape of a moving air-liquid interface in a perfect wetting channel has been investigated over a wide range of capillary numbers. The thickness of the film wetting the channel walls, its shape and the dynamic contact angle are extracted using the total reflection of the laser beam on the wetting film-air interface

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Taylor [12] and Bretherton [13] performed two of the most classic investigations on the creeping motion of elongated confined bubbles in horizontal tubes of small diameters (millimeter scale). They found that the thickness of the liquid film wetting the channel walls increases with the capillary number following a power law [14]. Based on experimental data, Taylor [12] proposed 1=2 for the exponent of the empirical power law.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taylor [12] and Bretherton [13] performed two of the most classic investigations on the creeping motion of elongated confined bubbles in horizontal tubes of small diameters (millimeter scale). They found that the thickness of the liquid film wetting the channel walls increases with the capillary number following a power law [14]. Based on experimental data, Taylor [12] proposed 1=2 for the exponent of the empirical power law.…”
Section: Introductionmentioning
confidence: 99%
“…Bretherton's law matched his experimental data for Ca ¼ 10 À3 À 10 À2 . Since the works of Taylor [12] and Bretherton [13], a number of studies have examined the thickness of the liquid film surrounding a bubble or a drop during steady motion [15][16][17][18][19][20][21]14,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier research efforts have examined contact line evolution for droplets deposited on non-swelling gels, 21,22 in which there is no mass exchange between the substrate and the droplets. In such instances, where surface deformations occur strictly due to the vertical component of the surface tension force, substrate deformation has a significant effect on contact line dynamics of the fluid motion.…”
Section: Introductionmentioning
confidence: 99%
“…Each petal must then be πd/600 = 1 mm wide. A Position Sensitive Detector (PSD) could measure optical beam shifts up to 1 nm [25]. It would then correspond to a rotation angle of φ = 10 −9 rad, and a displacement of the mirror of 10 −16 m here.…”
mentioning
confidence: 99%